Contract farming and technical efficiency: evidence from low-value and high-value crops in Nepal - Mishra, Ashok K.; Shaik, Saleem; Khanal, Aditya R.; Bairagi, Subir (Wiley, 2018)
Contract farming (CF), an institutional innovation, can reduce transaction costs and solve market imperfections in many developing countries. This study compares productivity and technical efficiency (TE) of contract and independent producers of high yielding variety (HYV) paddy seed (a low‐value crop) and ginger (a high‐value crop) producers in a sample of smallholders in Nepal. We address the self‐selection into CF by using propensity score matching and translog stochastic frontier function to estimate our empirical model. Using farm‐level data from Nepal, our findings show that CF increased the average TE levels of HYV paddy seed producers from 87% to 94% and the average TE levels of ginger producers from 89% to 97%. Finally, we find that human capital and distance to the market increases the technical inefficiency of low‐value crop smallholders in Nepal. [EconLit citations: C21, O13, Q12].